1987
DOI: 10.1002/bjs.1800740508
|View full text |Cite
|
Sign up to set email alerts
|

Splenectomy in the management of haematological disease

Abstract: Patients, both adults and children, with various haematological disorders who had splenectomy electively in the diagnosis, staging or treatment of their condition during a 15-year period in the Aberdeen hospitals were reviewed. The outcome regarding the disease and the immediate and long-term complications of splenectomy in this group of 185 patients are presented. Splenectomy has an acceptably low morbidity, even in patients with serious haematological disease, in the hands of an experienced surgical team, wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
16
0
2

Year Published

1990
1990
2017
2017

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(18 citation statements)
references
References 36 publications
0
16
0
2
Order By: Relevance
“…Laparoscopic splenectomy produced a clinically significant platelet response in 82% of patients with ITP in this series, which is consistent with response rates of 62% to 83% quoted for open splenectomy for ITP. [10][11][12][13] Response occurred in 72% of ITP patients by the time of discharge. Significant Nonetheless, the possibility of serious complications or death exists after splenectomy, regardless of the operative approach, as illustrated by the 4.7% mortality rate oflaparoscopic splenectomy in this series.…”
Section: Discussionmentioning
confidence: 99%
“…Laparoscopic splenectomy produced a clinically significant platelet response in 82% of patients with ITP in this series, which is consistent with response rates of 62% to 83% quoted for open splenectomy for ITP. [10][11][12][13] Response occurred in 72% of ITP patients by the time of discharge. Significant Nonetheless, the possibility of serious complications or death exists after splenectomy, regardless of the operative approach, as illustrated by the 4.7% mortality rate oflaparoscopic splenectomy in this series.…”
Section: Discussionmentioning
confidence: 99%
“…Literature shows post splenectomy complications rate ranging from 12% to 52% while mortality rates ranging from 1% to 9%. For example, Musser et al 12 reported a complication rate of 25% and mortality rate of 5%, Dawson et al 13 reported a morbidity of 25%, and mortality of 1%, Similarly, Johansson et al 14 described various complications in 14.5% patients with mortality of 1%. Recent studies show more favorable results, like Kojouri et al, in an analysis of 3386 splenectomies, reported a complication rate of 9·6% for laparoscopic splenectomy and 12·9% for open splenectomy, while associated mortality rates were very low, at 0·2% and 1% respectively.…”
Section: Discussionmentioning
confidence: 99%
“…18,19 Morbidity rates rise to 14%-50% in open splenectomy (OS) and to 20%-60% in splenomegaly cases treated with OS, but morbidity rates are comparable with normal cases when applying LS. 2 Moreover, whereas most laparoscopic studies reported minor complications such asileus, seromas of the port site, and pleural effusion, OS presents a high prevalence of severe complications such as subphrenic abscess requiring surgery (3%-5%), severe bleeding (5%-7%), and pulmonary embolism (2%-6%). 20 Finally, LS reduces intraoperative risk and postoperative complications most of all in older patients or patients presenting either comorbidity, malignancies, splenomegaly, or other factors that would lead us to consider them at high risk.…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3] Splenectomy has been performed for a heterogeneous group of hematologic diseases with a therapeutic or diagnostic purpose or as part of the staging process in Hodgkin's disease. Splenectomy has proved to be safe and effective in selected patients presenting non-Hodgkin's lymphoma, idiopathic thrombocytopenic purpura, thrombotic thrombocytopenic purpura, and hairy cell leukemia.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation